Strengthening Apparatus Competence to Improve Local Tax and Retribution Services in the Gorontalo Regency Government - Mahmud, Widyawaty; Rustam Tohopi; Alfiyah Agussalim (Universitas Negeri Semarang, 2025)
Abstrak This study aims to analyze the self-development competency of apparatus in providing local tax and retribution services at the Regional Revenue Agency of Gorontalo Regency. Apparatus competence is a strategic factor for realizing high-quality public services, increasing taxpayer compliance, and supporting the achievement of Local Own-Source Revenue (PAD). This research employed a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation involving 15 informants consisting of apparatus and taxpayers, and analyzed through data reduction, presentation, and conclusion drawing using source triangulation. The findings show that: (1) in terms of training and self-development, training activities have improved knowledge and skills in tax administration and public service, although their implementation remains uneven and unsustainable; (2) regarding the ability to adapt to technological and system changes, apparatus demonstrate strong readiness and willingness to operate digital systems such as SIPADA, SIPENDA, and TE RANO despite limited facilities and capability gaps; and (3) in terms of self-evaluation, apparatus are beginning to build reflective work habits through the implementation of SKP and the ASN e-Performance system, which positively impacts discipline and service accuracy, although integration into institutional policy remains limited.